Manisnya Inovasi Herbal: Pelatihan Pembuatan Permen Jelly Jahe sebagai Camilan Fungsional Lokal di Nagari Batu Kalang Utara - Dillasamola, Dwisari; Yufri Aldi; Zozy Aneloi Noli; Uce Lestari; Dehan Fahresta; Abdullah Muhammad Faathir; Aditya Gufashar; Afifah Hulwah; Andhini Aurellyta Ridwan; Fashelia Azizaturrahmah; Habib Shidiq Akbar; Iva Rama Fitria; Larisa Aurellia Vilonia; Lusi Octaviana; Muhammad Fazly; Muhammad Abdul Najib; Muhammad Aidi Satryo; Muhammad Rahil Dief; Nadhira Yuri Maharani; Novita Sari; Saniya De Nafisa; Widya Faizatul Zuhri; Vika Permata Gustam; Yudistio Arnoza; Zainini Arraysa (Jurnal Pengabdian Harapan Ibu (JPHI), 2025)
The community service activity aimed to enhance public understanding and skills in utilizing ginger (Zingiber officinale) as a natural ingredient for functional food through the production of jelly candy. This initiative was motivated by the low level of public knowledge, as indicated by pre-test results showing limited understanding of the health benefits and processing techniques of ginger. The activity consisted of educational sessions, demonstrations, and hands-on practice on jelly candy production using natural ingredients, including ginger extract, sugar, jelly powder, vanilla, salt, and cinnamon. Evaluation through post-tests, interactive quizzes, and observation of practical sessions demonstrated a significant improvement in participants’ knowledge and skills. Participants showed enthusiasm and were able to independently produce ginger-based jelly candy. This program not only increased public literacy on the use of herbal ingredients but also encouraged the development of small-scale functional snack enterprises. Future implementations are expected to expand to other communities with continuous mentoring to strengthen economic and health impacts.